KAJIAN BENTUK DAN MAKNA TATA RIAS, BUSANA, DAN AKSESORIS TOKOH DEWI SEKARTAJI PADA UPACARA ADAT CEPROTAN DI DESA SEKAR KOTA PACITAN - Verina Mayang Sari; Lutfiati, Dewi; Kusstianti, Nia; Wilujeng, Biyan Yesi (Jurnal Tata Rias, 2024)
This research aims to determine the form and meaning of (1) facial make-up (2) hair styling (3) clothing (4) accessories for the figure of Dewi Sekartaji at the Ceprotan traditional ceremony. The research method uses a qualitative descriptive approach. Data collection techniques use interviews, observation and documentation. The results of the research on Dewi Sekartaji's make-up are: (1) base makeup, light colored powder, mangot eyebrows meaning beautiful brown curves, green eyeshadow meaning fertility and yellow meaning wisdom. Nose shading is dark brown, blush is red and pink. Double stacked eyelashes, black and white eyeliner. Chili red lip blush, godeg sungu embu. The meaning of facial makeup shows the character of Dewi Sekartaji who was full of devotion throughout her life. (2) Hair styling using a bun sticking up means high aspirations and flowing hair symbolizes the long journey that has been taken. (3) Clothing includes; kemben, kace, and batik skirts from tumurun revelation mean getting a gift. Cover skirt. The meaning of green clothing means abundant fertility in Sekar village. (4) Accessories include; The mountains mean the majesty of God, the siger-shaped crown symbolizes the Goddess Sekartaji throughout the land of Java, the sumping sticks out upwards, the red tendrils of the shoulders mean strength. Belts, bracelets, buttocks, sampurs and scarves. The overall meaning of gold accessories is prosperity, white symbolizes a kind character and positive aura and green is a harmony in make-up and clothing. Keywords: Makeup, Goddess Sekartaji, Ceprotan Traditional Ceremony